Characterization of Starch from Some New Cassava Accessions at Different Maturity - Williams, Gifty (2018)
A thesis submitted to the Department of Food Science and Technology, College of Science in partial fulfilment of the requirements for the degree of Master of Science in Food Science and Technology.